Physico-chemical characteristics of the seasonally flooded soils of Bangladesh and their management implications - Akhter, KF; Khan, ZH; Hussain, MS; Mazumder, AR (Dhaka University Journal of Biological Sciences, 2011)
The seasonally flooded soils of Bangladesh are unique in respect of several specific characteristics and contribute toward producing bulk of its staple food - mainly rice. Having fine texture these soils are similar to the “paddy soils” of Southeast Asian floodplains and have high production potential under proper management. Six representative soil series, viz. Arial, Debidwar, Naraibag, Jalkundi, Siddirganj and Tippera from the central region of Bangladesh have been studied to evaluate some of their intrinsic physico-chemical properties and their sustainable management requirements. These soils are slightly acidic to neutral and are negatively charged with ΔpH values ranging between –0.2 and –1.2. The organic matter content in the surface soil is relatively low that decreases steadily with depth. The cation exchange capacity (CEC) of the soils varies on the basis of their clay and organic matter contents while base saturation per cent (BSP) is high. The contents of available N, P, K and S and DTPA-extractable Fe, Mn, Cu and Zn in soils are moderate and are commensurate with the contents of colloidal fractions. These soils receive several mineral nutrients annually with the sediments deposited during the monsoon floods. The characteristics like organic matter content, particle size distribution, CEC, pH and BSP that have important management implications have been discussed. Key words: Seasonally flooded soils; Physical and chemical attributes; Management implications DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8978 DUJBS 2011; 20(2): 173-182